FROM RITUAL TO REASONING: EXPLORING ETHNOMATHEMATICAL CONCEPTS IN THE NGAWU-AWU CULTURAL TRADITION - Muhamad Syahdan Sa'id; Deny Hadi Siswanto; Kintoko Kintoko (CV. Denasya Smart Publisher, 2026)
This study aims to examine and describe the mathematical concepts embedded in the Ngawu-awu tradition in Gunung Kidul Regency as part of an ethnomathematical inquiry. The research employed a qualitative approach with an ethnographic–ethnomathematical design. The research participants consisted of traditional leaders, village elders, tumpeng makers, and community members directly involved in the implementation of the tradition, selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and documentation, and subsequently analyzed using thematic analysis. The findings reveal that the Ngawu-awu tradition embodies a comprehensive application of mathematical concepts, including geometry in the arrangement of tumpeng and uborampe (cones, circles, and symmetry), arithmetic and ratios in the distribution of agricultural yields, patterns and sequences in the scheduling of agricultural rituals, as well as measurement and estimation in communal rice field cleaning activities. These findings confirm that mathematics exists as a form of contextual intelligence integrated into the cultural practices of the community. Therefore, the Ngawu-awu tradition holds significant potential to be utilized as a contextual, meaningful, and culturally grounded source for ethnomathematics-based learning